Measuring the photodetector frequency response for ultrasonic applications by a heterodyne system with difference- frequency servo control - Koch, Christian (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2010)
A technique for the calibration of photodiodes in ultrasonic measurement systems using standard and cost-effective optical and electronic components is presented. A heterodyne system was realized using two commercially available distributed feedback lasers, and the required frequency stability and resolution were ensured by a difference-frequency servo control scheme. The frequency-sensitive element generating the error signal for the servo loop comprised a delay-line discriminator constructed from electronic elements. Measurements were carried out at up to 450 MHz, and the uncertainties of about 5% (k = 2) can be further reduced by improved radio frequency power measurement without losing the feature of using only simple elements. The technique initially dedicated to the determination of the frequency response of photodetectors applied in ultrasonic applications can be transferred to other application fields of optical measurements